A CRITICAL EXAMINATION OF THE NEOCLASSICAL ECONOMIC PARADIGM AND ITS EXPLANATORY POWER ON GLOBAL INCOME INEQUALITY - Anton Abdulbasah Kamil; Dede Hertina (CV. Fahr Publishing, 2024)
This study critically examines the theoretical limitations of the neoclassical economic paradigm in explaining global income inequality, particularly in the context of a post-pandemic, digitized, and ecologically unstable world. The research aims to deconstruct core neoclassical assumptions—such as marginal productivity theory, rational individualism, and market neutrality—and assess their relevance to contemporary inequality dynamics. Employing a qualitative method through a structured literature review of 50 high-impact academic and institutional sources, this study uses thematic content analysis to synthesize interdisciplinary critiques from political economy, ecological economics, and post-colonial theory. The findings reveal that neoclassical models fail to account for structural drivers of inequality, such as historical legacies, institutional asymmetries, digital labor dynamics, and capital accumulation beyond productivity. While neoclassical economics remains influential in shaping global development agendas, its ideological persistence often legitimizes unequal outcomes rather than resolving them. The novelty of this research lies in its conceptual framework, which integrates fragmented critiques into a cohesive theoretical challenge to economic orthodoxy and links inequality to global issues like platform labor, climate migration, and fiscal erosion. As global inequality deepens despite overall economic growth, this study highlights the urgent need to shift towards more pluralistic and inclusive economic thinking. In conclusion, rethinking foundational economic theory is critical to formulating policies that promote equity, sustainability, and justice on a global scale.